Root resorption of adjacent teeth due to maxillary impacted canines – comparative analysis of the findings on cone beam computed tomography and panoramic imaging - Simić, Sanja; Nikolić, Predrag V.; Pavlović, Jasna; Vukićević, Vladanka; Vujačić, Amila (Vojnosanitetski pregled, 2023)
Background/Aim. A frequently reported phenomenon associated with impacted maxillary canines is root resorption (RR) of the adjacent teeth. The reported incidence of RR also depends on the radiographic imaging method used. The aim of the study was to evaluate the correlation between two radiographic methods: panoramic imaging (orthopantomogram – OPT) and cone beam computed tomography (CBCT), in diagnosing contact between the impacted canine with the adjacent teeth and the existence of their resorption. Methods. The study included 64 subjects aged 12 to 33 years, with 80 impacted maxillary canines not orthodontically treated previously. Positions of impacted maxillary canines and possible RR of adjacent teeth were firstly estimated on the OPT and then on the CBCT. Results. The estimated prevalence of RR of permanent teeth was significantly different concerning the estimation of OPT and CBCT imaging. RR of the adjacent teeth was found in 25% of the OPT but in 66.25% of the CBCT. The lateral incisor was the tooth most commonly affected by RR. It is especially important to emphasize that premolar resorption was not detected at all using OPT. Conclusion. There was a highly significant difference between OPT and CBCT analysis concerning the relationship between the impacted canine and adjacent teeth and their possible resorptions. CBCT is a more accurate and precise examination method compared to OPT for determining the localization of impacted teeth and the possible presence of RR in the adjacent teeth.